New Economic Statecraft: China, the United States and the European Union - Zhang Xiaotong (Routledge, 2024)
This book provides insights on the art of governing a state and managing its external relations from a wealth-power logic. It looks at ""economic statecraft"", which consists of wealth production, wealth mobilization, and wealth-power conversion by a state. This book reconceptualizes what economic statecraft is and proposes a new theory focused on wealth-power conversion. With a long historic perspective, this book goes through the modern history of Western powers practicing economic statecraft since 1500, and presents three case studies, the United States, the European Union, and China, the three biggest users of economic statecraft in the contemporary world. The book serves as an ideal reference for policy makers, businesspeople, and researchers whose work touch upon either wealth creation, power projection, or the combination of both.
Keywords: 330; economic security; foreign direct investment; geo-economics; strategic competition; trade investment